2017
DOI: 10.1136/bjophthalmol-2017-310731
|View full text |Cite
|
Sign up to set email alerts
|

5-year disease progression of patients across the glaucoma spectrum assessed by structural and functional tools

Abstract: BackgroundAssessment of spectral-domain optical coherence tomography (SD-OCT) compared with visual fields, to detect progression across the glaucoma spectrum.MethodsIn this study, adult glaucoma suspects and patients, with baseline retinal nerve fibre layer (RNFL) thickness on SD-OCT and reliable visual field (VF) tests on Humphrey Field Analyser (HFA) prior to March 2010, were recruited. Functional and structural progression over at least 5 years was compared using Glaucoma Progression Analysis (GPA) and VF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Clinically, there was no significant progression difference among the three clusters in VF tests. This is probably due to the fact that the majority of patients enroled in this study were at an early to moderate stage, and structural abnormalities in OCT were preceded by functional abnormalities in the VF test [18][19][20]. In early to moderate glaucoma, glaucomatous changes are typically detected in OCT before VF defects occur [17,[21][22][23].…”
Section: Discussionmentioning
confidence: 94%
“…Clinically, there was no significant progression difference among the three clusters in VF tests. This is probably due to the fact that the majority of patients enroled in this study were at an early to moderate stage, and structural abnormalities in OCT were preceded by functional abnormalities in the VF test [18][19][20]. In early to moderate glaucoma, glaucomatous changes are typically detected in OCT before VF defects occur [17,[21][22][23].…”
Section: Discussionmentioning
confidence: 94%
“…In our study, an average of 2.18 OCT per patient had been performed over 5 years of follow-up. About double of this average was reported by Seth et al [13] in 2017 in India who has reported 4.2 OCT per patient. The low number of OCT performed in our study could be due to financial reasons [14] and the difficulty of honoring control appointments by patients.…”
Section: Discussionmentioning
confidence: 73%
“…1.05% per year in our study. Seth et al [13] found a loss of 2.90% and 2.61% on average per year, respectively in the upper and lower quadrants. This discrepancy could be explained by the age difference between the samples, younger in our study, 48 years against 54 years in Seth's sample [13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Medeiros et al [ 74 ] also followed GS for a median of 6.7 years and concluded that RGC loss in glaucomatous eyes compared to controls had 28% loss on average at the earliest VF defect on SAP. With the inclusion of a disease continuum from GS to advanced glaucoma, other recent longitudinal studies showed that OCT endpoints, i.e., pRNFL [ 75 , 76 ] and GCC [ 75 ], had good detection of progression in early glaucoma, whereas macular measures, i.e., GCC, were better biomarkers in advanced glaucoma stages.…”
Section: Commonalities and Complementarities Of The Modalities Oct And Electrophysiologymentioning
confidence: 99%